2020
DOI: 10.1021/acs.iecr.0c00453
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed ZIF-8 Monoliths for Biobutanol Recovery

Abstract: We report the use of 3D-printed ZIF-8 adsorbent monoliths for the recovery of biobutanol from model fermentation mixtures. Two ZIF-8 monoliths, obtained by layer-by-layer printing, with different fiber thickness (250 and 600 μm), front channel size (350 μm × 350 μm and 760 μm × 760 μm), and side channel size (<60 and 260 μm) were studied. Equilibrium isotherms of acetone−butanol−ethanol (ABE) fermentation products showed that both monoliths retained a high saturation capacity (0.2 g/g) for n-butanol and a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 91 publications
(153 reference statements)
0
31
0
Order By: Relevance
“…First, the measurement of the variation in adsorbed amount in time and along one spatial dimension of the column underpins the design of robust processes for separations with stringent specifications, such as ultra-high purity products (Hosseinzadeh Hejazi et al 2017). Second, the need to intensify current industrial pressure-temperature swing adsorption processes relies, among others, on the improvement of heat and mass transport through the design of contactor geometries that cannot be captured with traditional one-dimensional models (Claessens et al 2020;Sharma et al 2020;Wurzbacher et al 2016). While three-dimensional modelling of complete pressure-(PSA), vacuum-(VSA), and temperature-swing adsorption (TSA) cycles is nowadays possible (Gautier et al 2018;Lian et al 2019;Qasem and Ben-Mansour 2018), these findings would need to be validated against direct measurements of time-resolved internal adsorbent loading profiles in three-dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the measurement of the variation in adsorbed amount in time and along one spatial dimension of the column underpins the design of robust processes for separations with stringent specifications, such as ultra-high purity products (Hosseinzadeh Hejazi et al 2017). Second, the need to intensify current industrial pressure-temperature swing adsorption processes relies, among others, on the improvement of heat and mass transport through the design of contactor geometries that cannot be captured with traditional one-dimensional models (Claessens et al 2020;Sharma et al 2020;Wurzbacher et al 2016). While three-dimensional modelling of complete pressure-(PSA), vacuum-(VSA), and temperature-swing adsorption (TSA) cycles is nowadays possible (Gautier et al 2018;Lian et al 2019;Qasem and Ben-Mansour 2018), these findings would need to be validated against direct measurements of time-resolved internal adsorbent loading profiles in three-dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…More advanced adsorber designs, such as those using layered beds (Sircar and Golden 2006) or structured adsorbents (DeWitt et al 2018;Sharma et al 2020) provide for an additional level of complexity in the design of the separation process. While it is now computationally feasible to model cyclic adsorption processes in 3D with computational fluid dynamics approaches (Gautier et al 2018;Lian et al 2019;Qasem and Ben-Mansour 2018), such models have so far mostly been applied to cylindrical homogeneous packings; their extension would enable the description of contactor geometries that cannot be captured by traditional onedimensional models (Claessens et al 2020;Sharma et al 2020;Wurzbacher et al 2016). These advanced numerical approaches would greatly benefit from the development of experimental methods that enable the direct measurement of transient concentration profiles in adsorbent columns.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations were carried out for both, to reveal that fully unblocked side channels helped to obtain a uniform gas distribution throughout the structure. Furthermore, the study showed how the full capacity of the ZIF‐8 monoliths was restored upon thermal regeneration [46] …”
Section: Three‐dimensional Printed Materials Based On Coordination Bomentioning
confidence: 99%
“…The synthesis of the 3D-printed ZIF-8 monolith and its performance in the adsorption of butanol has already been published in earlier work (Lefevere et al, 2019;Claessens et al, 2020). The monolithic adsorbent was supplied by VITO and produced using a 3D-printing fiber deposition method ( Figure 1).…”
Section: Materials Propertiesmentioning
confidence: 99%
“…From these measurements, the mean pore diameter was calculated to be 0.37 µm. Complete data on the pore volume can be found in previous work (Lefevere et al, 2019;Claessens et al, 2020). A water adsorption isotherm was determined at 25°C by means of a gravimetric technique (VTI, TA Instruments, New Castle, PA).…”
Section: Materials Propertiesmentioning
confidence: 99%